Negative Ecologies : Fossil Fuels and the Discovery of the Environment - Bond, David (University of California Press, 2022)
So much of what we know of clean water, clean air, and now a stable climate rests on how fossil fuels first disrupted them. Negative Ecologies is a bold reappraisal of the outsized role fossil fuels have played in making the environment visible, factual, and politically operable in North America. Following stories of hydrocarbon harm that lay the groundwork for environmental science and policy in North America, this book brings into clear focus the dialectic between the negative ecologies of fossil fuels and the ongoing discovery of the environment. Exploring iconic sites of the oil economy, ranging from leaky Caribbean refineries to deepwater oil spills, from the petrochemical fallout of plastics manufacturing to the extractive frontiers of Canada, Negative Ecologies documents the disruptions, injuries, and disasters that have long accompanied fossil fuels and the manner in which our solutions have often been less about confronting the cause than managing the effects. This history of our present promises to re-situate scholarly understandings of fossil fuels and renovate environmental critique today. David Bond challenges us to consider what forms of research, critique, and mobilization may now be needed not only to confront the deleterious properties of fossil fuels, but to envision ways of living beyond them.